2002
DOI: 10.1074/jbc.m203799200
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis Reveals Alterations in the Renal Kallikrein Pathway during Hypoxia-Induced Hypertension

Abstract: Obstructive sleep apnea syndrome (OSAS), a disorder characterized by episodic hypoxia (EH) during sleep, is associated with systemic hypertension. We used proteomic analysis to examine differences in rat kidney protein expression during EH, and their potential relationship to EH-induced hypertension. Young male Sprague-Dawley rats were exposed to either EH or sustained hypoxia (SH) for 14 (EH14/SH14) and 30 (EH30/SH30) days. Mean arterial blood pressure was significantly increased only in EH30 (p < 0.0002). Ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
43
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 50 publications
10
43
0
1
Order By: Relevance
“…One of the altered proteins with the greatest magnitude of change was calbindin-D28k, whose expression level increased 6.7-fold in diabetic kidney, as determined by 2-D proteomic analysis. Although MALDI-TOF MS followed by peptide mass fingerprinting is not a definitive protein identification method, we have frequently demonstrated that proteins identified by this method, with careful analysis using a vigorous scoring system to determine a significant hit (match), are consistent with those identified by other methods, especially 1-D and 2-D Western blot analyses [15,16,[19][20][21]. In the present study, the MALDI-MS-based proteomic data were again confirmed by Western blot analysis.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…One of the altered proteins with the greatest magnitude of change was calbindin-D28k, whose expression level increased 6.7-fold in diabetic kidney, as determined by 2-D proteomic analysis. Although MALDI-TOF MS followed by peptide mass fingerprinting is not a definitive protein identification method, we have frequently demonstrated that proteins identified by this method, with careful analysis using a vigorous scoring system to determine a significant hit (match), are consistent with those identified by other methods, especially 1-D and 2-D Western blot analyses [15,16,[19][20][21]. In the present study, the MALDI-MS-based proteomic data were again confirmed by Western blot analysis.…”
Section: Discussionsupporting
confidence: 75%
“…Protein extraction from the whole kidney was performed as described previously [15,16]. Briefly, the kidney was rapidly frozen in liquid nitrogen, ground to powder, resuspended in a buffer containing 50 mM Tris, 0.3% SDS, and 200 mM DTT, and incubated at 100 °C for 5 min.…”
Section: Extraction Of Renal Proteinsmentioning
confidence: 99%
“…292 In addition, intermittent hypoxia induces the sympathetic nervous system to increase vascular resistance, downregulates expression of the kallikrein-kallistatin vasodilator Shelley Transforming growth factor β inhibition 446 Pro-fibrotic metalloproteinase inhibition 447 Anti-fibrotic metalloproteinase activation 447 Destabilization of renal Remote ischemic pre-conditioning [384][385][386][387][388][389][390] hypoxia-inducible factor Prolyl hydroxylase inhibition 244,448 von Hippel-Lindau protein inhibition 449 pathway, and activates the renal renin-angiotensin-aldosterone system to cause vasoconstriction. [293][294][295][296][297][298][299] Together these processes conspire to produce renal fibrosis and sustained hypertension and their associated means of reducing renal oxygenation ( figure 1). 82,[300][301][302][303][304] Oxygenation is further compromised by nocturnal hypoxia altering parasympathetic control of heart rate and inducing left ventricular hypertrophy.…”
Section: Repeated Episodes Of Acute Kidney Injurymentioning
confidence: 99%
“…49,[379][380][381] The targeting of vasoconstriction pathways controlled through vasopressin, endothelin, and voltage dependent calcium channels are in their infancy, as is the use of vasodilators such as arginine and kallikrein. 155,250,268,298,379,382,383 Beyond systemic hypooxygenation and vasoconstriction, the hypoxia-dependent processes of microvascular rarefaction, oxidative stress, leukocyte recruitment, and fibrosis all contribute to the development of CKD. A host of potential therapeutic targets exists within these areas (Table 1).…”
Section: A New Hypoxia Paradigmmentioning
confidence: 99%
“…Neutrophil lysates were subjected to isotype control or anti-Akt immunoprecipitation. Immunoprecipitated proteins were initially resolved by high-resolution 2D-PAGE as previously described by our group (22,23). MALDI analysis coupled with BLASTP analysis of Akt immunoprecipitates identified a C-terminal fragment of GABA B R2, as an Akt binding protein.…”
Section: Proteomic Analysis Of Akt Immunoprecipitatesmentioning
confidence: 99%